EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN QUIZIZZ TERHADAP HASIL BELAJAR BAHASA ARAB SISWA KELAS XI DI MAN 2 KOTA BENGKULU - Herlina, Osika; Nurhidayat, Nurhidayat; Dari, Ikke Wulan (JURNAL ILMIAH EDUNOMIKA, 2024)
Quizizz is a media in the form of a webtool that is believed to motivate students in learning activities with an attractive menu. The purpose of this study is to determine the effectiveness of the use of quizizz media on learning outcomes in Arabic subjects, The method used is a quantitative method with a quasi-experimental approach. The sample in this study is 60 people, namely all students in classes XI A and XI H. Data collection techniques with tests. The results of this study are in the effective category. This can be seen from the test results of the N-gain score of 77.16%, the minimum N-gain score of 41.83%, and the maximum N-gain score of 100.00%. So it can be concluded that quizizz learning media is effective in improving student outcomes.